Evaluation of the effectiveness and efficiency of the state control: labor relations - Elena I. Dobrolyubova (Статистика и экономика)
Improving the efficiency and effectiveness of state control is a key priority of the governance in Russia. In this connection special importance is the clear definition of the concepts and the criteria development for performance assessment and the effectiveness of state control according to the reform objectives and reflecting the final, meaningful results of its implementation for the society.The article reviews the approaches for defining of the effectiveness and the efficiency of state control both in Russia and internationally. Based on this analysis, the article proposes comprehensive definition of the state control effectiveness, which includes preventing, damage minimization and damage reimbursing to publicly significant values. Based on these definitions evaluating criteria are proposed and approved for the example of state control in the sphere of labor relations.The results of this evaluation show, despite the generally positive trend, the protection level of the values, protected by the law in this area is significantly inferior to the European, especially in terms of mortality on production and economic losses associated with occupational injuries.Overall, the implementation of the methodic approach, proposed in the article would help to overcome the repressive nature of state control in Russia, change the emphasis from revealing violations to minimizing publicly significant risks in the state control areas.